The production potential of Kikuyu (Pennisetum clandestinum) pastures over-sown with Ryegrass (Lolium spp.) - Truter, Wayne Frederick (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2010.